(untitled) (American Journal of Interdisciplinary Research and Innovation, 2025)
The outdated background of the teachers handling Araling Panlipunan poses problems that internalize and aggravate learning outcomes and the education system. Subject mastery, effective teaching and student interest are some areas lacking for most unqualified teachers. The purpose of this study was to determine how out-of-field Araling Panlipunan teachers out of these difficulties and what strategies they used to cope. A qualitative phenomenological approach was chosen and data were collected from ten teachers who were teaching outside their specialization from secondary schools in Lutayan District 1 and 2 in the Division of Sultan Kudarat. Through insufficient content knowledge subject mastery, a lack of sufficient appropriate pedagogy, professional conflict and role construction curriculum interface and resource insufficiency were all gaps thoroughly analyzed. These gaps were addressed through self-directed learning,instructional research,team work and practice teaching, which resilience accompanied with technology helps. With all barriers facing educators, they personally saw value in transforming their teaching practices resulting in them becoming more devoted to teaching, fostering strong emotional relationships with students, and broadening the scope of education towards facilitating learners from all backgrounds. Based on the findings, an Enhanced Pedagogical Approach Professional Development Course was designed to provide comprehensive support for out-of-field teachers. Teachers employed self-directed learning, research, collaboration, adaptive instruction, resilience, and technological integration to address these difficulties. Despite these challenges, teachers gained valuable professional insights, including personal transformation, continuous learning, enhanced student connections, and a stronger commitment to inclusive and accessible education. Based on these findings, a Professional Development Course was designed to equip out-of-field teachers with enhanced pedagogical approaches, curriculum adaptation strategies, and role adjustment techniques to improve instructional effectiveness. This study underscores the importance of structured training, institutional support, and capacity-building programs in addressing the needs of out-of-field teachers and ensuring quality education.